Uso de un modelo de aguas someras para analizar la influencia del Atlántico Tropical Norte y del Pacı́fico Ecuatorial del Este sobre la circulación atmosférica en los mares Intra-Americanos - Alfaro Martínez, Eric J. (2007)
A shallow water model was used to simulate the anomalous circulation over the Intra American Seas (IAS), due to heat forcing fun ctions located at the Tropical North Atlantic and the Eastern Equatorial Pacific Oceans, respectively.Despite of its simplicity, the shallow water model represented the main features of the anomalous circulation over the IAS due to the heat forcing functions described previously. The main anomaly patterns were observed when heat sources have opposite signs across the IAS, e.g. Tropical North Atlantic cool (warm) and Eastern Equatorial Pacific warn (cool). Results imply an increase (a decrease) in the vertical wind shear over the IAS for a cool (warm) Tropical North Atlantic and a warm (cool) Eastern Equatorial Pacific. These patterns could be associated with a larger (smaller) vertical wind shear over the IAS.